Dampak Kecemasan Terhadap Kemandirian Lansia: Deskriptif Literature Review - Intan Savitri; Hastin Trustisari (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
. Background: Anxiety is a common mental disorder frequently experienced by the elderly and can affect various aspects of their lives, including independence. Independence, defined as the ability to perform daily activities without assistance from others, is a crucial element in the quality of life of the elderly. A high level of independence allows the elderly to maintain self-esteem, reduce dependence on others, and enhance their psychological well-being. Objective: This study aims to describe and analyze the long-term negative impact of anxiety on the independence of the elderly. Methods: This study uses a descriptive literature review method. Literature was searched through Google Scholar with keywords: independence, anxiety, and elderly. Results: The literature indicates that anxiety has a significant long-term negative impact on the independence of the elderly. Elderly individuals with high levels of anxiety tend to experience difficulties in performing daily activities, avoid physical activity, and face an increased risk of depression. Conclusion and Recommendations: Anxiety affects the independence of the elderly through physical and mental impacts as well as indirect mechanisms such as decreased motivation and social isolation. Strategies and interventions should focus on improving the overall quality of life of the elderly with a holistic approach that addresses physical, mental, and social health.